2012
DOI: 10.1111/j.1365-3040.2012.02508.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock‐induced biphasic Ca2+ signature and OsCaM1‐1 nuclear localization mediate downstream signalling in acquisition of thermotolerance in rice (Oryza sativa L.)

Abstract: We investigated heat shock (HS)‐triggered Ca2+ signalling transduced by a Ca2+ sensor, calmodulin (CaM), linked to early transcriptome changes of HS‐responsive genes in rice. We observed a biphasic [Ca2+]cyt signature in root cells that was distinct from that in epicotyl and leaf cells, which showed a monophasic response after HS. Treatment with Ca2+ and A23187 generated an intense and sustained increase in [Ca2+]cyt in response to HS. Conversely, treatment with Ca2+ chelator, L‐type Ca2+ channel blocker and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 76 publications
4
71
0
Order By: Relevance
“…Recent work suggested that an unfolded protein response also exists in the chloroplast (Yu et al, 2012;Schmollinger et al, 2013;Ramundo et al, 2014). Plasma membrane fluidity has been identified as an important temperature sensor in land plants that appears to lie upstream of the unfolded protein response (Sangwan et al, 2002;Suri and Dhindsa, 2008;Saidi et al, 2009;Wu et al, 2012). Increased membrane fluidity appears to open calcium channels in the plasma membrane and inflowing calcium to trigger signaling cascades, including an H 2 O 2 burst (Königshofer et al, 2008), leading to the activation of the HS response.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggested that an unfolded protein response also exists in the chloroplast (Yu et al, 2012;Schmollinger et al, 2013;Ramundo et al, 2014). Plasma membrane fluidity has been identified as an important temperature sensor in land plants that appears to lie upstream of the unfolded protein response (Sangwan et al, 2002;Suri and Dhindsa, 2008;Saidi et al, 2009;Wu et al, 2012). Increased membrane fluidity appears to open calcium channels in the plasma membrane and inflowing calcium to trigger signaling cascades, including an H 2 O 2 burst (Königshofer et al, 2008), leading to the activation of the HS response.…”
Section: Introductionmentioning
confidence: 99%
“…During the process of evolution, plants have developed the antioxidant system, including antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), guaiacol peroxidase (GPX) and ascor-bate peroxidase (APX), as well as low-molecular weight water-soluble antioxidants ascorbic acid (AsA) and glutathione (GSH), to maintain ROS homeostasis in plant cells (Foyer & Noctor 2009Jaleel et al 2009;Ahmad et al 2010;Szarka et al 2012;Garg & Kaur 2013). Therefore, the balance between ROS and antioxidant system plays crucial role in the acquisition of heat stress in plants (Wahid et al 2007;Ahmad et al 2010;Saidi et al 2011;Mittler et al 2012;Szarka et al 2012;Wu et al 2012). However, the effect of hydrogen sulfide treatment on heat tolerance of maize seedlings in relation to antioxidant system is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Among these stress factors, high temperature is a major abiotic factor affects metabolism, growth, development, reproduction, yield, and even survival of plants including crop plants like maize (Zea mays L.) (Li & Gong 2011;Saidi et al 2011;Mittler et al 2012;Wu et al 2012;Grover et al 2013;Piterková et al 2013). In crop plants, maize not only is a new model plant, but also the third most important food grain crop after wheat and rice, and heat stress is the principal cause of maize failure worldwide, global warming accentuates this problem (Leipner & Stamp 2009;Strable & Scanlon 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations